Children's posture and muscle activity at different computer display heights and during paper information technology use. - Straker L; Burgess-Limerick R; Pollock C; Coleman J; Skoss R; Maslen B; Straker, Leon; Burgess-Limerick, Robin; Pollock, Clare; Coleman, Jemma; Skoss, Rachel; Maslen, Barbara (Human Factors, 2008)
Objective: The 3-D posture and muscle activity in the neck and upper limb were assessed in children using high-, mid-, and book-level displays, which correspond to working conditions frequently observed when children interact with computers or books and paper.Background: The 3-D posture and muscle activity of children reading and inputting data with computers and paper had not been previously assessed.Methods: Twenty-four children aged 10 to 12 years and of normal height performed an interactive task involving reading from a book and writing on paper or reading from a computer display and inputting data using a mouse and keyboard.Results: Head and neck flexion increased as the visual target was lowered. The high display resulted in mainly upper cervical relative extension, and the book display resulted in both upper and lower cervical flexion. The book condition resulted in greater cervical erector spinae and upper trapezius activity than did the mid and high conditions.Conclusion: The data suggest that a mid-level display may be more appropriate for children than a high display (e.g., when the display is placed on top of the central processing unit). The mid display also results in a more upright and symmetrical posture and lower mean muscle activity than does working with books and paper flat on the desk.Application: This study provides short-term laboratory study evidence for the formulation of guidelines for workstation design and adjustment for children. Use of computers by children is increasing, yet ergonomic guidelines lag behind those for adults.